Estado nutricional e a síndrome da fragilidade em idosos usuários da atenção básica - Stürmer, Jaqueline (2016)
The frailty syndrome (SF) is one of the phenomenon resulting from the aging process, which can carry greater institutionalization rates, morbidity, functional decline and death. Moreover, elderly people go through changes at the same time as they are physiological and natural aging may become more susceptible to elderly nutritional disorders, worsening their general health. This study aimed to evaluate the nutritional status and SF in elderly users of primary care in Marau/RS, through a cross-sectional study. They evaluated 148 elderly aged 65 or older, users of public health care facilities, residents in the municipality and who agreed to sign the Informed Consent and Informed (IC). The elderly were assessed for phenotype of frailty, sociodemographic, clinical, anthropometric and cognitive. Nutritional status was assessed by body mass index (BMI) and the Mini Nutritional Assessment (MNA). Of the elderly evaluated (n = 148), 72.3% were female. The average age was 73,6 years (±5,92), ranging between 65 and 89 years. Were classified as frail 16,2%, 45,3% as pre-frail and 38,5% non-frail. The weakness was significantly associated with age (p=0,002), education (p=0,000), smoking (p=0,035) and nutritional status assessed by MNA (p=<0,001). By applying the MNA, an elderly was classified as malnourished, 90,5% were considered normal nutritional status (n=134) and 8,78% were at risk of malnutrition (n=13) .The mean BMI was 28,79kg/m2, considered overweight for seniors. There was no significant association between BMI and fragility. The criteria of the phenotype of frailty that appeared more frequently were the slowness and low grip strength. These findings highlight the importance of assessing nutritional status, as well as the fragility criteria in elderly patients using the Basic Health Care, aiming at effective actions to prevent, control and treat certain conditions that might lead the elderly to functional decline